Republic of Rwanda : Report on the Observance of Standards and Codes--Accounting and Auditing - World Bank (World Bank, Washington, DC, 2016)
The Report on the Observance of Standards and Codes - Accounting and Auditing (ROSC A&A) program is part of a 12-module joint World Bank-IMF initiative to assist member countries to strengthen their financial systems by improving their capacity to comply with internationally recognized standards and codes. The program focuses on the institutional framework underpinning national accounting and auditing practices, and degree of conformity with international standards and good practices. The initial ROSC A&A for Rwanda was carried out in 2008 and provided a key input in designing necessary financial reporting reforms in the country. The 2015 update is a valuable tool for monitoring the effectiveness of the reform program. It assesses the degree to which the recommendations of the 2008 ROSC A&A review have been implemented, identifies issues that have emerged since the last review, and proposes a number of recommendations aimed at further strengthening the quality of corporate financial reporting and auditing which contributes to improving business climate, investors’ confidence and economic growth potential of Rwanda.